Primary Nasal Transmissible Venereal Tumour in a Geriatric Dog - Andressa Ilvia de Souza Fagundes; Valquíria Tatiele da Silva Rodrigues; Joana de Souza de Cardoso; Eviny Rodrigues de Oliveira; Jeicielly Oliveira dos Santos; João Paulo Vitoria do Nascimento; Alves da Silva Vieira, Layze Cilmara (Acta Scientiae Veterinariae, 2024)
Background: The Transmissible Venereal Tumour (TVT) is a round cell neoplasm that affects dogs. Its localisation is predominantly venereal; however, it can be found in extragenital regions, such as skin, nostrils, mouth and eyes. This paper describes a case of nasal TVT in a geriatric dog, performing its clinical, laboratory, therapeutic and prognostic analysis. Case: A 13-year-old male dog, mixed breed, non-castrated, domiciled, weighing 19,200 kg, was attended at the Small Animal Medical Clinic (CMPA) of the University Veterinary Hospital (HVU) of the Multidisciplinary Centre of the Barra Campus, Federal University of Western Bahia (UFOB), presenting cachexia, reactive lymph nodes except the popliteal ones, dehydration, dyspnoea, arrhythmia, frequent sneezing with serous and yellowish nasal discharge, cough, difficulty in breathing, increased volume in the face (left nasal plane), enlarged volume above the right eye with a suppurative wound just below. The animal’s haemogram revealed the presence of normocytic normochromic anaemia, neutrophilic leukocytosis with left regenerative shift and hyperproteinaemia. The serum biochemical tests for renal function (urea and creatinine) and hepatic function (ALT, AST and AF) showed normal levels. The cytological evaluation showed a monomorphic population of large cells with a round nucleus, condensed chromatin and 1 to 2 prominent nucleoli, abundant and slightly basophilic cytoplasm, with multiple punctuated vacuoles, showing discrete anisocytosis and anisokaryosis and mitotic figures, confirming a case of TVT. In addition, the presence of neutrophils was evidenced, indicating an inflammatory process. Simultaneously, an X-ray of the skull was requested, which was not returned. A chemotherapy protocol was instituted using vincristine sulphate [0.025 mg/kg IV], for 5 sessions with an interval of 1 week between each session, clinical and laboratory monitoring of the regression of neoplastic cells, demonstrating total efficacy. It is worth noting that after the 2 nd application of the pharmaceutical, the animal presented adverse reactions, with clinical symptoms of emesis, decreased appetite and weight loss; so, the animal was then subjected to fluid therapy, treatment with immunostimulants, appetite stimulants and antiemetics, which influenced its clinical improvement. Discussion:The importance of complementary diagnostic tests in the routine of veterinary clinics and hospitals is noticeable, aimed at establishing the diagnosis and therapeutic monitoring of diseases. In the present report, diverging from the majority of cases described in the literature, the animal showed signs of neoplasia at 13 years of age, in a context of reduced sexual activity. It is believed that the fact that he has free access to the street and has olfactory habits inherent to the canine species in terms of contact with the genital region of other animals, left him exposed to factors that determined the transmissibility of the neoplasm. Weekly clinical follow-up as well as laboratory tests, was essential to ascertain the effectiveness of the treatment, the presence of adverse reactions and the introduction of new drugs. The normocytic normochromic anaemia possibly occurred in response to the nodular and haemorrhagic characteristics of the tumour tissue. The leukocytosis due to neutrophilia and hyperproteinaemia would be related to the occurrence of an acute infectious process, probably bacterial. It is concluded that although geriatric patients present immunosuppression more easily than other age groups, in cases of TVT, the therapeutic approach with vincristine sulphate, and the clinical and laboratory follow-up adopted influence the good prognosis concerning neoplastic regression. Keywords: TVT, neoplasia, neoplasm, neoplastic disease, elderly, old dog